Volume 5: Industrial and Cogeneration; Microturbines and Small Turbomachinery; Oil and Gas Applications; Wind Turbine Technolog 2010
DOI: 10.1115/gt2010-22680
|View full text |Cite
|
Sign up to set email alerts
|

Tip Leakage in Small Radial Turbines: Optimum Tip-Gap and Efficiency Loss Correlations

Abstract: The tip-leakage flow mechanisms in turbocharger turbines used for downsized internal combustion engines and the associated losses are investigated over a range of operating conditions. Experiments are performed on a small, 35 mm diameter turbocharger turbine with varying tip-gap heights in a turbocharger test facility and numerical simulations are presented for extending the parameter range to sizes not covered experimentally. The sensitivity of turbine efficiency to tip-gap is evaluated and correlations for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In radial turbomachinery it has been modeled mainly depending on the rotational speed by Spraker [19] and further by Baines [18] applying the observation of different flow patterns in different zones by Dambach et al [15]. Also empirical approximations have been introduced by Wallace [20] and later generalized by Kammeyer et al [21]. Although much research has been done in the field of turbine tip leakage modeling yet, the need of fitting to broad range data and later extrapolation towards extreme off-design condition requires a novel model which can estimate losses at different rotational speeds and loadings.…”
Section: Introductionmentioning
confidence: 99%
“…In radial turbomachinery it has been modeled mainly depending on the rotational speed by Spraker [19] and further by Baines [18] applying the observation of different flow patterns in different zones by Dambach et al [15]. Also empirical approximations have been introduced by Wallace [20] and later generalized by Kammeyer et al [21]. Although much research has been done in the field of turbine tip leakage modeling yet, the need of fitting to broad range data and later extrapolation towards extreme off-design condition requires a novel model which can estimate losses at different rotational speeds and loadings.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of CFD results with different tip gap heights in Figure 4.33 and in Figure 4.34 shows that this geometry change can influence significantly the turbine efficiency and rather less reduced mass flow. This has also been stated by Kammeyer et al [63]. From the wide range data it can further be seen that the difference in efficiency diminishes towards very low pressure ratios/high BSRs with varying tip gap height.…”
Section: Geometrical Influence On Tip Leakage Flow Characteristicssupporting
confidence: 83%
“…Also the radial inducer section and thus the axial tip gap is barely existing in current turbocharger turbine designs. All this makes especially the turbocharger turbine efficiency prone to tip leakage losses as confirmed by Kammeyer et al [63]. Hence, the modeling of the losses and a detailed knowledge of the main physical effects are of high interest for one-dimensional modeling and turbine design.…”
Section: D Tip Leakage Modelingmentioning
confidence: 95%
See 1 more Smart Citation
“…The flow is driven by the pressure difference between the suction and pressure surface. Kammeyer et al [34] showed that this effect accounted for as much as 7% of the turbine total-to-static efficiency, t-s. In this paper, an empirical model that was suggested by Japikse and Baines [20] was used and it is shown in Equations 18 and 19.…”
Section: Formentioning
confidence: 99%